Assessment of resident Canada goose management in Kansas - Malanchuk, John Louis II (Kansas State University, 2021)
Resident Canada geese (Branta canadensis, geese nesting in the conterminous United States) was one of the many wildlife species declining by the early 1900s due to large-scale human disturbance (e.g., overharvest and habitat destruction). After decades without recognized breeding populations, many thought resident Canada geese were extinct in Kansas and the rest of the United States. Today, certain populations of resident Canada geese are so abundant they can be a nuisance; especially during spring breeding season. Resident Canada geese provide intrinsic value to Kansans as well as economic value through hunting licenses, travel, lodging, and taxes leveed on guns and ammunition. My goal was to address information gaps necessary to make science-based management decisions for resident Canada geese in Kansas. My objective for the first chapter was to determine the effect of translocation on urban-banded nuisance geese. My objective for the second chapter was to assess potential changes to the statewide spring breeding population survey for nesting geese in Kansas, to reduce bias and variation while maintaining or reducing survey cost. My objective for the third chapter was to determine the effect of latitude on age-class specific recovery patterns for resident Canada geese in the eastern tier of the Central Flyway. I estimated survival and recovery probabilities from hunter-harvested band recoveries for normal and translocated (i.e., urban geese relocated to rural areas) resident Canada geese. Annual survival differed between normal (S ̂ = 0.761, 95% CI 0.734-0.785) and translocated (S ̂ = 0.598, 95% CI 0.528-0.665) geese. Recovery probability also differed between normal and translocated adults (normal wild f ̂ = 0.074, 95% CI = 0.069-0.078; translocated f ̂ = 0.138, 95% CI = 0.120-0.158) and juveniles (normal wild f ̂ = 0.067, 95% CI = 0.059-0.075; translocated f ̂ = 0.250, 95% CI = 0.199-0.310). Recovery probability did not differ between status in the sub-adult age class (normal wild f ̂ = 0.126, 95% CI = 0.115-0.137; translocated f ̂ = 0.090, 95% CI = 0.055-0.144). Since 2014, Kansas Department of Wildlife and Parks has used fixed-wing aircraft to survey 160 1-mi² plots in 2 landcover strata (80 high and 80 medium strata) based on expected abundance of breeding Canada geese. I used survey data from 2019 to estimate change in bias of potential plot reallocation scenarios focusing on inter-plot count variation. I simulated design scenarios by reallocating plots in groups of 10 (e.g., 90 medium, 70 high). I simulated each scenario 100 times and calculated density and associated standard deviation, 90% confidence intervals, and coefficient of variation (CV) for each iteration. The top-ranked survey design based on the greatest reduction in bias predicted reallocating 40 medium stratum plots to the high strata would be the most effective method to increase statistical power and reduce coefficient of variation. Finally, I investigated the effects of banding latitude (i.e., banding state) and age-class on geospatial recovery patterns of resident Canada geese in the eastern-tier states of the Central Flyway, 2012–2019. I used optimized hot spot analyses and inverse distance weighting to measure how recoveries of sub-adult and adult geese differed spatially as insight into latitudinal effects of molt migration. Sub-adult geese from southern-banding states were recovered disproportionately at more northerly latitudes than sub-adult geese from northern banding states. Adult geese were disproportionately recovered in their respective banding state. These results will be used to inform the Kansas Department of Wildlife and Parks revision of the state resident Canada goose management plan.
Keywords: Branta canadensis; Canada geese; Kansas; Molt migration; Survey simulation; Wildlife